Intra-tracheal gene delivery of aerosolized SERCA2a to the lung suppresses ventricular arrhythmias in a model of pulmonary arterial hypertension. (February 2019) - Strauss, Benjamin; Sassi, Yassine; Bueno-Beti, Carlos; Ilkan, Zeki; Raad, Nour; Cacheux, Marine; Bisserier, Malik; Turnbull, Irene C.; Kohlbrenner, Erik; Hajjar, Roger J.; Hadri, Lahouaria; Akar, Fadi G.
Abstract: Background: Pulmonary arterial hypertension (PAH) results in right ventricular (RV) failure, electro-mechanical dysfunction and heightened risk of sudden cardiac death (SCD), although exact mechanisms and predisposing factors remain unclear. Because impaired chronotropic response to exercise is a strong predictor of early mortality in patients with PAH, we hypothesized that progressive elevation in heart rate can unmask ventricular tachyarrhythmias (VT) in a rodent model of monocrotaline (MCT)-induced PAH. We further hypothesized that intra-tracheal gene delivery of aerosolized AAV1.SERCA2a (AAV1.S2a), an approach which improves pulmonary vascular remodeling in PAH, can suppress VT in this model. Objective: To determine the efficacy of pulmonary AAV1.S2a in reversing electrophysiological (EP) remodeling and suppressing VT in PAH. Methods: Male rats received subcutaneous injection of MCT (60 mg/kg) leading to advanced PAH. Three weeks following MCT, rats underwent intra-tracheal delivery of aerosolized AAV1.S2a (MCT + S2a, N = 8) or saline (MCT, N = 9). Age-matched rats served as controls (CTRL, N = 7). The EP substrate and risk of VT were determined using high-resolution optical action potential (AP) mapping ex vivo. The expression levels of key ion channel subunits, fibrosis markers and hypertrophy indices were measured by RT-PCR and histochemical analyses. Results: Over 80% of MCT but none of the CTRL hearts were prone to sustained VT by rapid pacing (P < .01). Aerosolized gene delivery of AAV1.S2a to the lung suppressed the incidence of VT to <15% (P < .05). Investigation of the EP substrate revealed marked prolongation of AP duration (APD), increased APD heterogeneity, a reversal in the trans-epicardial APD gradient, and marked conduction slowing in untreated MCT compared to CTRL hearts. These myocardial EP changes coincided with major remodeling in the expression of K and Ca channel subunits, decreased expression of Cx43 and increased expression of pro-fibrotic and pro-hypertrophic markers. Intra-tracheal gene delivery of aerosolized AAV1 carrying S2a but not luciferase resulted in selective upregulation of the human isoform of SERCA2a in the lung but not the heart. This pulmonary intervention, in turn, ameliorated MCT-induced APD prolongation, reversed spatial APD heterogeneity, normalized myocardial conduction, and suppressed the incidence of pacing-induced VT. Comparison of the minimal conduction velocity (CV) generated at the fastest pacing rate before onset of VT or at the end of the protocol revealed significantly lower values in untreated compared to AAV1.S2a treated PAH and CTRL hearts. Reversal of EP remodeling by pulmonary AAV1.S2a gene delivery was accompanied by restored expression of key ion channel transcripts. Restored expression of Cx43 and collagen but not the pore-forming Na channel subunit Nav1.5 likely ameliorated VT by improving CV at rapid rates in PAH. Conclusion: Aerosolized AAV1.S2a gene delivery selectively to the lungs ameliorates myocardial EP remodeling and VT susceptibility at rapid heart rates. Our findings highlight for the first time the utility of a non-cardiac gene therapy approach for arrhythmia suppression.